Optimum space frames with rectangular plans - Mushchanov Vladimir; Mushchanov Alexander; Orzhehjvskiy Anatoliy; Tcepliaev Maxim (Magazine of Civil Engineering, 2023)
In this article, the object of research is spatial framed systems, one of the most commonly used types of spatial structures. The main feature of the research is the expansion of proven design solutions to the area of large-span frames with rectangular plan with an aspect ratio of less than 1:2, which is an urgent research and practical task. In this regard, the main purpose of the research study is to establish a connection between the main parameters of the projected object (geometric characteristics, structural loads) and their metal intensity. The study was based on a number of research methods. We used the finite element method in the numerical study of the coating stability of rods loaded in the axial direction. The method of physical modeling helped in experimental studies of models and coatings of their elements. Finally, the method of optimal design, specifically the Nelder–Mead method, was used to find the basic shape of a structure with a long-span rectangular plan. Main results. First, the data from theoretical and experimental studies confirmed a decrease in the estimated length of the compressed elements by 5...25 % due to their partial pinching in the ball nodes-connectors. Secondly, we developed an optimal design algorithm of spatial frames with long-span rectangular plans with an aspect ratio of less than 1:2. It differs from the previously developed ones due to a clarification of the load-carrying ability of axially loaded rods from the stability condition and the project designer's advanced capabilities in terms of their shaping. It provides an opportunity to use clear correspondences at the trial design stage and to clarify the specific metal consumption to set the optimal geometric parameters of the projected structure. We found patterns that make it possible to design optimal material consumption flat and spatial structural forms of spatial frames on rectangular large-span plans with an aspect ratio of less than 1:2, while taking into account the refined bearing capacity of rods loaded in the axial direction. The results obtained make it possible to use a proven limited range of structural elements in the form of round-section rods and connecting elements (ball-and-socket plug-connectors).